SOME REPRODUCTIVE CHARACTERISTICS OF FEMALE Clarias gariepinus EXPOSED TO DIETS CONTAINING Bryophyllum pinnatum LEAF - ALIMI, A.A; IKENWEIWE, N.B.; EZERI, G.N.O.; BANKOLE, M.O. (Nigerian Journal of Fisheries, 2020)
The utilization of medicinal plants as alternatives to synthetic materials as pro-fertility has been highly harnessed. Phytochemical analysis of Bryophyllum pinnatum leaf (BL) and its nutritional effects on some reproductive characteristics of female Clarias gariepinus was determined. Fifty-six C. gariepinus sub-adults (482.48±18.27 g/fish) were fed seven iso-nitrogenous diets (30% CP) containing B. pinnatum leaf at varying levels: T1 (1gBL/100g), T2 (2gBL/100g), T3 (3gBL/100g), T4 (4gBL/100g), T5 (5gBL/100g), T6 (6gBL/100g) and Control (0gBL/100g). The results of the phytochemical analysis of B. pinnatum revealed the presence of medicinally active constituents with the highest concentration (µg/mL) in Steroid (116.85±0.03), then Saponin (37.00±0.58), Glycoside (10.30±0.12), Flavonoids (4.50±0.06), Tannin (2.35±0.03) and least in Phenol (0.18±0.00). These confirmed the possible use of B. pinnatum as a pro-fertility agent in fish. Reproductive indices of fish were evaluated after 28 weeks of feeding and spawning. Diets containing BL improved (p<0.05) egg weight (492.95±50.32g), fecundity (320417.50±32705.45), pseudo-gonadosomatic index (0.23±0.02) and % survivals (41.13±0.3) in T6, fertilization and hatchability % (67.45±1.64 and 47.50±1.44) in T4 compared to the Control. Conclusively, the study confirmed the presence of bio-active compounds of reproductive importance in B. pinnatum leaf and it can be included in C. gariepinus sub-adult diets up to 6% to enhance its reproductive characteristics.